ANALISIS PENGARUH TINGKAT KENAIKAN PENGGUNAAN CAPITAL EXPENDITURE TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Fitri, Isa Nur (Jurnal Akuntansi AKUNESA, 2014)
This research aims to analyze the effect of capital expenditure oncompany performance. Manufacturing company was used as a samplebecause this company do a lot?s of capital expenditure than nonmanufacturing firm?s. Changes in return on asset and capitalexpenditure were used as variable. The result showed that return onasset has a positive relationship to capital expenditure.Keywords: Capital expenditure, return on asset, companyperformance